Profile of Learning Independence in Achieving Creative Thinking Ability of Vocational School Students - Hikmah, Zia Nurul; Khairunnisa, Rohmatul Aulia; Nuriadin, Ishaq (Universitas PGRI Madiun, 2020)
This research focuses on the profile of learning independence in achieving the mathematical creative thinking skills of vocational school students. This research was conducted in class X SMK with subjects consisting of 5 students. Data collection techniques using questionnaires, tests, and interviews. Data analysis was carried out through data reduction, data presentation, data interpretation, and conclusion drawing. In this study, data reduction was carried out by grouping students into high, medium, and low levels of learning independence through a learning independence questionnaire. Furthermore, the data is presented with a description of the characteristics of the creativity level of students who have high learning independence in solving math problems. Then draw conclusions. Researchers used triangulation methods to compare data. The results of this study are that students have a high level of learning independence and students have difficulty working on tasks of mathematical creative thinking skills so that it takes a long time to do. Students are required to have activeness, own initiative, be resilient and persistence in learning. Students can involve various resources and activities such as reading alone, group study, and question exercises in order to improve their mathematical creative thinking skills